Analysis and design of 3D-printed flexure mechanism - Teo, Jeriel Zhi Jun (2018)
Compliant mechanisms (CM) are defined as monolithic, flexible structures that use elastic deformation to achieve desired motion. Such mechanisms are already being developed into myriads of micro- and nano-positioning applications all around us due to their ability to eliminate backlash and dry friction compared to their ball bearing or rigid-joint counterparts. CM are also preferred over traditional mechanisms for their high resolution, high repeatability in motion, hence use in precision and robotic applications, like micromanipulators in micro-electronic mechanism systems (MEMS). There are several characteristics of CMs that are desirable and can be harnessed, depending on their application. In some cases, the workspace needs to be maximised, while in other cases accuracy of motion is needed. This report presents a 3-DOF xyθz RRR compliant parallel mechanism designed for optimal stiffness performance- with exceptional translational and rotational stiffness ratios of 814 and 447 respectively and a large workspace of 3.5 by 3.5mm by 2.5o. The numerical solutions by Finite Element Analysis (FEA) were within ±8% of the analytical solutions as well. The mechanism was synthesised through a novel design approach combining the stiffness modelling based on the Pseudo-Rigid-Body Model (PRBM) and conducting optimisation for the optimal placement of the flexure notches for best stiffness performance. The model is then verified through FEA before a working prototype was manufactured to demonstrate the desired motion.